Scientific data sharing using clustered-based data sharing (CDS) in grid environment - Latip, Rohaya; Ibrahim, Hamidah; Al-Hanandeh, Feras Ahmad (Universiti Utara Malaysia, 2010)
In a large dynamic network, data can be shared and accessed in an easy manner among researchers from various locations and accessed provided an efficient protocol to manage the data. A protocol is needed to ensure the data is consistent and accessible. In this paper, we introduced a new protocol, named Clustered-based Data Sharing (CDS) for data sharing in a large dynamic network such as grid computing by using Clustered-based techniques to improve the accessibility. This is due to Clustered-based techniques can ensure that the data is accessible among the members of the grid. To evaluate our model, we developed a simulation model in Java. Our results show that CDS achieves high data accessibility even when the number of nodes or sites are increasing.